The Thebesian valve height/coronary sinus ostium diameter ratio (H/D-Ratio) as a new indicator for specifying the morphological shape of the valve itself in multisliced computed tomography. (15th December 2015) - Klimek-Piotrowska, Wiesława; Koziej, Mateusz; Hołda, Mateusz K.; Sałapa, Kinga; Kuniewicz, Marcin; Lelakowski, Jacek
Abstract: Background: The coronary sinus ostium (CSO) is covered by the Thebesian valve (ThebV), which has a variable shape when assessed subjectively. The ThebV is an anatomical barrier during CS cannulation, which may be complicated due to the valves' size. The types of valves are: cord, remnant, semilunar, fold, and mesh/fenestrated. The ThebV can be visible using multisliced computed tomography (MSCT), however, this method cannot show the ThebV's morphological shape, only its size. Methods: 301 randomly selected autopsied human hearts were examined. The shape of the valve was subjectively assessed, whereas the ThebV height (H) and the CSO diameter (D) were measured. The H/D-Ratio was computed as the ThebV height divided by the CSO diameter, afterwards k-means cluster analysis was performed to estimate H/D-Ratio's range of values between valves. MSCT scans from 114 patients that underwent CSO cannulation were objectively evaluated based on similar measured parameters in accordance with received H/D-Ratio values. Results: Boundaries of ratio evaluations between remnant and semilunar, and semilunar and fold types were 0.35 and 0.65 respectively. In MSCT scans, the ThebV was recorded in 61 cases (remnant = 5.3%, semilunar = 24.6%, fold = 16.7%, cord = 0.0%, mesh/fenestrated = 7.9%). Except for the remnant and cord types, the other types appear similarly as in the cadaveric and MSCT studies. There were no differences between ThebV height and the CSO diameter in cadavers and MSCT studies. Conclusion: The H/D-Ratio can be useful in assessing ThebV shape as visualized in MSCT. We give threshold values for the H/D-Ratio which easily allow the ThebV shape to be determined.